Meta-Analysis Study: The Influence of Project Based Learning Models on Creativity and Science Learning Outcomes of Elementary School Students - Sari*, Rona Taula; Angreni, Siska; Mohtar, Lilia Ellany; Lufri, Lufri; Asrizal, Asrizal; Hardeli, Hardeli (Universitas Syiah Kuala, 2024)
The project based learning (PjBL) model is expected to be able to change students' learning styles by increasing motivation in learning, creativity in work, generating creative ideas, and being able to think critically. The meta-analysis research aims to find out how big the effect of the PjBL model is on the creativity and science learning outcomes of elementary school students?; Does the implementation of the PjBL model affect the creativity and science learning outcomes of elementary school students? Collecting articles using the publish or perish application with the keywords PjBL model, creativity, and elementary science learning outcomes. The data obtained was analyzed by calculating the effect size of each journal. Analysis of the average effect size of 0.92 is in the large category. The PjBL model influences the creativity and learning outcomes of elementary school students with r RE = 0.925 in the high category. This shows that the PjBL model can increase student creativity and learning outcomes in elementary school science learning. The PjBL model can improve and develop creativity and high-level thinking skills based on the demands of the 4.0 era.